Tissue Reactions to Various Suture Materials Used in Oral Surgical Interventions. (8th May 2012) - Javed, Fawad; Al-Askar, Mansour; Almas, Khalid; Romanos, Georgios E.; Al-Hezaimi, Khalid
Abstract : A variety of suture materials are available for primary wound closure following oral surgical procedures. The aim was to review the tissue reactions to the various suture materials used in oral surgical interventions. Databases were searched using the following keywords: cotton, nylon, polyglecaprone 25, polytetrafluoroethylene (ePTFE), Polyglactin 910, polyglycolic acid (PGA), polylactic acid, silk, surgery, suture, and tissue reaction. Articles published only in English language were included. Seventeen studies were included. Two studies reported that polyglecaprone 25 had positive effects on wound-healing as compared to silk. Six studies reported that silk elicits more intense tissue inflammatory response and delayed wound healing as compared to other suture materials (including ePTFE, polyglecaprone-25, PGA, and nylon). Polyglactin 910 sutures were associated with the development of stitch abscess in one clinical study. Eight studies reported that tissue reactions are minimal with nylon sutures. Tissue reactions to suture materials used for oral surgical interventions may vary depending on the surface properties and bacterial adherence properties of the material.